Review: The Influence of Environmental Factors on Oil Quality and The Effectiveness of Various Extraction Methods in Producing Coffee Oil - Ilham Prasetyo Utomo; Fitry Tafzi; Mursalin Mursalin (Jurnal Multidisiplin Indonesia, 2026)
Coffee essential oil is a high-value derivative product of coffee beans with broad applications in the food, pharmaceutical, cosmetic, and aromatherapy industries. This study aims to analyze the influence of environmental factors on the chemical profile and quality of coffee oil, as well as to evaluate the effectiveness of various extraction methods based on the yields produced. The method employed is a systematic literature review of scientific literature published over the last ten years (2015–2025) and retrieved from the Google Scholar, ScienceDirect, MDPI, and PubMed databases. The results show that coffee oil quality is determined by multifactorial interactions related to terroir effects, including geographical origin, soil composition, climatic conditions, and altitude, all of which modulate the plant’s secondary metabolic pathways. Total phenolic acid and flavonoid contents reach optimal accumulation at moderate altitudes of approximately 1,400 meters above sea level, while soil mechanical structure significantly affects the concentration of key oil compounds. Regarding extraction methods, CO?-based supercritical fluid extraction provides the highest efficiency, achieving yields of up to 80% with optimal selectivity and purity, despite requiring substantial investment in equipment. Among solvent-based methods, ultrasonic-microwave-assisted extraction shows the best yield, reaching 10.58%. Conventional methods, such as mechanical pressing, Soxhlet extraction, and steam distillation, remain relevant for specific applications because of their operational simplicity. This review confirms that aligning extraction methods with the environmental conditions of the raw material’s origin is a key strategy for developing Indonesian coffee essential oil as a superior, high-value product in the global market.